2021
DOI: 10.1029/2020gl091168
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened Causal Connections Between the MJO and the North Atlantic With Climate Warming

Abstract: The Madden-Julian oscillation (MJO) has long been identified as an important source of midlatitude weather predictability on subseasonal-to-seasonal (S2S) timescales (∼2 weeks to 3 months) via its teleconnections to higher latitudes. Tropical convection associated with the MJO slowly propagates eastward in a quasiperiodic manner, taking ∼20-90 days to circumnavigate the globe and complete a cycle (Madden & Julian, 1971, 1972; Zhang, 2013). MJO activity can excite Rossby waves which propagate out of the tropics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
5
5
0
Order By: Relevance
“…The increase in the tropical dry static stability is a consequence of amplified upper-tropospheric warming that occurs as tropical temperatures adjust to warmer surface temperatures (e.g., Santer et al, 2005). Our first main finding is strong corroboration of the hypothesis that the increase in the tropical dry static stability is a robust thermodynamic response of the climate to warming that tends to reduce the MJO's teleconnections in almost all models (Fig.…”
Section: Mean Statesupporting
confidence: 75%
See 1 more Smart Citation
“…The increase in the tropical dry static stability is a consequence of amplified upper-tropospheric warming that occurs as tropical temperatures adjust to warmer surface temperatures (e.g., Santer et al, 2005). Our first main finding is strong corroboration of the hypothesis that the increase in the tropical dry static stability is a robust thermodynamic response of the climate to warming that tends to reduce the MJO's teleconnections in almost all models (Fig.…”
Section: Mean Statesupporting
confidence: 75%
“…That is, the MJO's circulation strength is directly proportional to its diabatic heating rate and inversely proportional to the dry static stability. It is expected that the tropical static stability will increase in the future as the tropical temperature profile adjusts towards the moist adiabatic lapse rate of a warmer surface (e.g., Santer et al, 2005). Ignoring changes to the MJO's precipitation intensity or its cloud optical properties (i.e., its diabatic heating rate), this will weaken the MJO's vertical circulation and its associated upper-level divergence.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2022). In the North Atlantic, increased skill is also consistent with research suggesting that the North Atlantic may become more sensitive to MJO teleconnections (Samarasinghe et al, 2021) and that the ENSO-North Atlantic Oscillation (NAO) teleconnection may strengthen (Drouard & Cassou, 2019;Fereday et al, 2020) in the future. The decrease in skill over the North Pacific is also consistent with recent research using a variety of CMIP6 models that suggests the ENSO teleconnection amplitude over the North Pacific may weaken in a warmer climate (e.g., Beverley et al, 2021;Fredriksen et al, 2020).…”
Section: Tropical Drivers Of Changing Midlatitude Skillsupporting
confidence: 81%
“…transferable this knowledge will be to a future, warmer climate. Therefore, research on subseasonal timescales has examined how the MJO (Maloney et al, 2018) and ENSO (Cai et al, 2021) will change in the future as well as the subsequent changes to their teleconnections (e.g., Beverley et al, 2021;Cui & Li, 2021;Drouard & Cassou, 2019;Fereday et al, 2020;Samarasinghe et al, 2021;W. Zhou et al, 2020;Z.-Q.…”
mentioning
confidence: 99%
“…Recent work has suggested that climate change will cause these waves to amplify in a way that increases the likelihood of concurrent heatwaves across important crop regions 8 , and summer weather may become more persistent 9 . Teleconnections associated with tropical rainfall and sea surface temperature variability, like El Niño and the Madden-Julian Oscillation, are also expected to change as a result, with amplified impacts on precipitation [10][11][12] .…”
mentioning
confidence: 99%